Enhanced Mental Reinstatement of Exposure to Improve Extinction Generalization: A Study on Claustrophobia and MRI Fear. Issue 1 (January 2023) - Carpenter, Joseph K.; Moskow, Danielle M.; Hofmann, Stefan G.
Highlights: Exposure therapy led to reduced claustrophobic fear in the treatment context. One week later, generalization of gains to a new context (a mock MRI) was tested. Before the test, participants revisited the exposure memory or a neutral memory. Revisiting the exposure memory reduced heart rate reactivity in the mock MRI. No differences in subjective fear or avoidance were found between conditions. Abstract: Fear of enclosed spaces prevents many people from receiving magnetic resonance imaging (MRI) scans. Although exposure therapy can effectively treat such fears, reductions in fear during exposure often do not generalize beyond the context in which they took place. This study tested a strategy designed to increase generalization, which involved revisiting the memory of a prior exposure to enhance retrieval of extinction learning. Forty-five participants with claustrophobia that included fear of MRI scans underwent a series of exposures lying inside a narrow cabinet. One week later, participants were randomly assigned to enhanced mental reinstatement (EMR) or control procedures. Prior to entering a mock MRI scanner, EMR participants recalled the memory of exposure training and listened to an audio recording of themselves describing what they learned, whereas control participants recalled a neutral memory. Compared to the control condition, EMR led to significantly reduced heart rate reactivity in the mock MRI scanner, but not self-reported fear or avoidance. There were no differences between conditions in claustrophobia symptoms or MRI fear at 1-month follow-up. Results suggest some benefits of mental reinstatement for improving generalization of gains following exposure training for claustrophobia, with measures of subjective fear and physiological arousal showing discordant outcomes.